Antibiofilm therapy in the treatment of respiratory infectious diseases caused by bacterial pathogens - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2018)
In a colonized environment, pathogenic bacteria change the form of existence from the planktonic to the microbiosocial, forming a peculiar structure, the so-called biofilm. The formation of biofilm is a key factor in the virulence of a wide range of pathogenic bacteria that cause both acute and chronic infections. The tolerance of biofilm bacteria to antibacterial agents underlies the majority of recurrent and chronic infectious diseases. Currently, therapeutic strategies are being developed to solve this problem. These strategies are aimed at suppressing the vital activity of biofilms. The therapeutic agents for protection against pathogenic bacterial biofilms are divided into two large groups. The first group are compounds that inhibit the formation of biofilms, and the second group are compounds that destabilize or destroy the structure of a mature formed biofilm. There is experimental evidence that the use of these drugs will be effective in the treatment of diseases associated with the formation of biofilms.